Association of Septic Shock with Mortality in Hospitalized COVID-19 Patients in Wuhan, China. (23rd April 2022) - Chen, Shaoqiu; Gao, Zitong; Hu, Ling; Zuo, Yi; Fu, Yuanyuan; Wei, Meilin; Zitello, Emory; Huang, Gang; Deng, Youping
Abstract : Purpose . Septic shock is a severe complication of COVID-19 patients. We aim to identify risk factors associated with septic shock and mortality among COVID-19 patients. Methods . A total of 212 COVID-19 confirmed patients in Wuhan were included in this retrospective study. Clinical outcomes were designated as nonseptic shock and septic shock. Log-rank test was conducted to determine any association with clinical progression. A prediction model was established using random forest. Results . The mortality of septic shock and nonshock patients with COVID-19 was 96.7% (29/30) and 3.8% (7/182). Patients taking hypnotics had a much lower chance to develop septic shock (HR = 0.096, p = 0.0014 ). By univariate logistic regression analysis, 40 risk factors were significantly associated with septic shock. Based on multiple regression analysis, eight risk factors were shown to be independent risk factors and these factors were then selected to build a model to predict septic shock with AUC = 0.956. These eight factors included disease severity (HR = 15, p < 0.001 ), age > 65 years (HR = 2.6, p = 0.012 ), temperature > 39.1°C (HR = 2.9, p = 0.047 ), white blood cell count > 10 × 10⁹ (HR = 6.9, p < 0.001 ), neutrophil count > 75 × 10⁹ (HR = 2.4, p = 0.022 ), creatine kinase > 5 U/L (HR = 1.8, p = 0.042 ), glucose > 6.1 mmol/L (HR = 7, p < 0.001 ), and lactate > 2 mmol/L (HR = 22, p < 0.001 ). Conclusions . We found 40 risk factors were significantly associated with septic shock. The model contained eight independent factors that can accurately predict septic shock. The administration of hypnotics could potentially reduce the incidence of septic shock in COVID-19 patients.